Incorporation of znck into an etch-and-rmse adhesive system on flexural strength, degree of conversion and bond durability to caries-affected dentin - Oliveira, C£rida Aurelia Rodrigues; Campos, Rosa Maria Peixoto; MacEdo, Julia Peixoto Campos; Silva, Anderson Rodrigo; Maximo, Leandro Neriton Candido; Silva, Tania Mara [UNESP]; Franca, Fabiana Mantovani Gomes; Basting, Roberta Tarkany; Turssi, Cecilia Pedroso; Goncalves, Sergio Eduardo De Paiva [UNESP]; Amaral, Flavia Luclsano Botelho (My University, 2019)
Purpose: To evaluate the effect of a zinc chloride (ZnCh) solution (2% wt), incorporated into a two-step etch-and-rinse adhesive system (AS), on microtensile bond strength (^iTBS) to caries-affected dentin (CAD). Methods: First, the degree of conversion (DC) of the AS with and without the ZnCh solution was evaluated by Fourier transform infrared spectroscopy (FT1R). Second, beam-shaped samples (7 mm x 2 mm x 1 mm) were prepared with the AS containing the ZnCh solution to perform flexural strength (FS) tests. For [iTBS testing purposes, CAD surfaces were etched with phosphoric acid and randomly divided into three groups (n=10): ZnCh-AS with ZnCl2; NT (no treatment)-AS without ZnCh; and CHX-pretreatment with 2% chlorhexidine solution. AS (Adper Single Bond 2) was applied according to the manufacturer's instructions, and resin composite restorations were built up. After 24 hours, the resin-dentin blocks were sectioned into specimens (0.8 mm2), and then subjected to jiTBS testing immediately following, or after 6 or 12 months of water storage (WS). The adhesive interface was evaluated by scanning electron microscope. Both nTBS and FS tests were performed using a universal testing machine (0.5 mm/minute). FS and DC data were submitted to the Student t-test, and jxTBS data were subjected to two-way ANOVA and Tukey's test (a= 0.05). Results: DC was not affected by ZnCh incorporation into AS (P= 0.2527). Higher FS values were obtained in the group with ZnCh added to AS. Regarding ^iTBS, the mean of the NT group was statistically higher than that of the ZnCh or the CHX groups (P< 0.001), regardless of WS, but the latter groups did not differ from each other. ^TBS at 24 hours was statistically superior to that of 6 and 12 months of WS (P< 0.001). (Am J Dent 2019;32:299-305).